Dharma and the Religious Other in Hindi Popular Cinema Journal for Religion, Film and Media - Kerry San Chirico (Journal for Religion, Film and Media, 2020)
This essay examines common representations of religious minorities in Hindi popular cinema within the context of dominant post-Independence Indian religious and political ideologies-from a religiously pluralist secular socialist framework to a Hindu nationalist late capitalist orientation. We begin by examining the more recent turn to film as a legitimate conveyor of middle-class Indian values worthy of interpretation, and the coeval shift among Indians from embarrassment to pride in film as the industry followed the liberalizing nation-state onto the global stage. Equipped with this interpretive strategy, we turn to the dhārmik, or religious elements within the Hindi sāmājik, or social film, demonstrating concretely how particular notions of Hindu dharma (variously if imperfectly translated as "duty," "law," "cosmic order," "religion") have long undergirded Hindi popular cinema structurally and topically. Finally, and most significantly, we examine representations of religious minorities, particularly Muslms, Christians, and Sikhs, in Hindi popular cinema against the backdrop of evolving religious and cultural ideologies up to the electoral victory of Prime Minister Modi of the Hindu nationalist Bharatiya Janata Party, or BJP. It is argued that minority representation, like other aspects of Indian public life, can be interpreted as an index of majority concerns about the religious Other. While such representations have never been static, more current depictions present the viewer with a troubling, even ominous picture of the place (or lack thereof) of religious minorities in contemporary Indian society, revealing majoritarian chauvinism and sectarian tensions that call into question the identity of the Indian Republic as a pluralistic secular nation, as well as the easy elisions between Hindu and secular Indian nationalisms. When we now look at past films cognizant of the Hindu nationalist dispensation to come, discontinuity is not the only striking feature. Ideological inconsistencies, tensions, and contradictions have long been manifest on the silver screen, particularly with regard to the religious minorities. The present ascendance of Hindutva as a national (indeed international) religio-political ideology forces us to reconsider past films and the ideologies embedded therein.